Depressive disorders in patients with pathologic of mammary - N. V. Poleschuk (Бюллетень сибирской медицины)
We examined of 116 patients with chronic cystic mastitis, 38 patients with malignant mammary neoplasm, and 29 patients without any pathologic of mammary. We estimated complaints of patients their life and medical history, and depression which was estimated by scales of Beak. In our research depression disorder dominates in group patients with chronic cystic mastitis - 49%, in group with breast cancer it consists — 34%, and in control group — 35%.